2017
DOI: 10.19128/turje.318064
|View full text |Cite
|
Sign up to set email alerts
|

Examining of biology subjects in the science textbook for grade 7 regarding scientific content

Abstract: For students, textbooks are a source of knowledge and an important learning material. For this reason, textbooks must contain appropriate content. In this research, our aim was to examine of biology subjects on secondary school 7 th grade science textbook in terms of scientific content. The data were analyzed using document analysis. Based on criteria such as the book's scientific content, knowledge deficiency, erroneous information and misrepresentations, three experts in the field of biology were assigned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
1
18
0
4
Order By: Relevance
“…When the findings were examined, it was determined that there were errors in terms of scientific knowledge, alternative concept, multiple answers, scientific fiction and measurement technique. When the literature is examined, it has been observed that there are similar findings about unit evaluation questions in the textbooks (Gündüz et al, 2016;Yılmaz et al, 2017a;Yılmaz et al, 2017b;Yılmaz et al, 2018).…”
Section: Findings Discussion and Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…When the findings were examined, it was determined that there were errors in terms of scientific knowledge, alternative concept, multiple answers, scientific fiction and measurement technique. When the literature is examined, it has been observed that there are similar findings about unit evaluation questions in the textbooks (Gündüz et al, 2016;Yılmaz et al, 2017a;Yılmaz et al, 2017b;Yılmaz et al, 2018).…”
Section: Findings Discussion and Resultsmentioning
confidence: 81%
“…Research has shown that the elimination of misconceptions in students is more difficult than learning new concepts (Atıcı, Samancı and Özel, 2007). It is known that the errors in the textbooks have negative effects on students' concept learning (Eyidoğan and Güneysu, 2002;Gündüz, Yılmaz and Çimen, 2016;Kurt, 2013;Ünsal and Güneş, 2002;Yeşilyurt and Gül, 2012;Yılmaz et al, 2017a). For this reason, it is very important to identify the situations that may cause misconceptions in students and to make studies to eliminate this situation.…”
Section: Introductionmentioning
confidence: 99%
“…Yılmaz et al (2018: 615) found that there was a lack of conceptuality about species richness and species diversity in the 10th grade textbooks. Concept confusion in the textbooks causes misconceptions in students and pre-service teachers (Yılmaz et al, 2017a).…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%
“…The misconceptions of the students were found to result from observations and media (Murat et al, 2011). Research on textbooks has shown that they contain scientifically incorrect and inaccurate information, thereby causing students to develop misconceptions (Yılmaz et al, 2017;Yılmaz et al, 2018). Kabapınar (2007) reported that students from primary education to university education had misconceptions and further discussed that pre-university education and textbooks are important factors behind this result.…”
Section: Post-application Findings On the Alternation Of Generationsmentioning
confidence: 99%